THE EFFECT OF SPIRITUAL-HYPNOTHERAPY ON BEHAVIORAL CHANGES IN RESIDENTS OF THE BHAYANGKARA INDONESIA DRUG ABUSE PREVENTION REHABILITATION INSTITUTE SURABAYA - Indah Sari, Sinta; Nasruddin (Program Studi Bimbingan dan Konseling FKIP UNJA, 2026)
Drug abuse is a complex problem that impacts an individual's physical, psychological, social, and spiritual aspects. Behavioral change is an important indicator of the success of rehabilitation counseling services for drug abusers. This study aims to analyze the effect of spiritual-hypnotherapy on behavioral changes in residents of the bhayangkara indonesia drug abuse prevention rehabilitation institute surabaya. The study used a quantitative approach with a pre-experimental method through a one-group pretest–posttest design. The study subjects were six inpatient rehabilitation residents selected using a purposive sampling technique. Data collection was conducted using a Likert scale questionnaire to measure behavioral change and the University of Rhode Island Change Assessment (URICA) scale to identify readiness for change. Data analysis used descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-Test. The results showed a significant difference between behavioral change scores before and after the spiritual- hypnotherapy intervention (p < 0.05). These findings indicate that spiritual-hypnotherapy is effective as a rehabilitative counseling intervention in encouraging adaptive client behavioral change. This research contributes to the development of a spiritual-based educational counseling approach in drug abuse rehabilitation services.